Perbandingan Analsa Kapasitas Sambungan Balok - Kolom Konvensional Dan Pracetak Sistem U-Shell (Studi Kasus Gedung A Rumah Sakit Pendidikan Universitas Riau) - Nasrullah Nasrullah; Zulfikar Djauhari; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Precast concrete construction have a lot of excellence compared to conventional system. this system excellence, for example well guaranted quality, produce quickly and mass, development which quickly, natty and environmental friendliness with good product quality. Precast system which have been proven by its excellence is certifiable and become solution to replace conventional system. That is seen to the number of building in Pekanbaru used precast system. One other newest is building University of Riau Educational Hospital. This hospital use precast concrete type U-Shell. The part that becoming attention from precast system is beam- column connections. Beam-column connections represent very important part in transferring forces precast element jointed. When is not planned better hence the connection can collapse of precast structure, so that can alter hierarchy which wish reached structure. This research have compared to momen and shear capacities between conventional beam- column connection and precast U-Shell. The result that obtained is difference of maximum confined concrete stress at corner connection (A), eksterior (B) and the interior (C) that is equal to 49,98 Mpa, 50,41 Mpa and 51,31 Mpa. Total of confined moment capacities is equal to A = 587,38 kN.m, B = 632,83 kN.m and C = 745,60 kN.m. The difference of maximum concrete stress and moment capacities of connection resulted from difference of configuraton of longitudinal steel and difference number of beam that connecting A, B And C that is 2, 3 and 4 of beams. Keywords : precast, u-shell, conventional, confined, connection